PERFORMANCE IMPROVEMENT OF PARTIALLY HYDROLYZED POLYACRYLAMIDE (PHPAM) BY MODIFIED ORGANOSILANE FOR ENHANCED OIL RECOVERY (EOR) APPLICATION - Arifin, Ihsan
In old oil wells, there is a decline in oil production so that the exploitation process is considered uneconomical. Therefore, it is necessary to increase oil recovery, called as Enhanced Oil Recovery (EOR). In the EOR technique, injection fluid such as surfactant solution or polymer solution is carried out. Both types of fluid have a role as a displacing agent for the remaining oil between the rock gaps. Until now, the most widely used polymer in EOR is polyacrylamide (PAM) and its derivatives due to its wide application and ease of modification of its compounds. Partially hydrolyzed polyacrylamide (PHPAM) is a PAM derivative which is proven to have high viscosity at low concentrations. However, PHPAM has a weakness in the form of its vulnerability to high salinity and temperature. In order to improve its thermal resistance and salinity properties, various modifications were carried out to PAM, such as adding sulfonate groups, grafting, and copolymerization. In addition to the above modifications, currently nanoparticles are also being developed as a mixture of EOR agents to improve polymer characteristics. Silica (nanosilica), alumina, and titanium oxide nanoparticles are some examples of nanoparticles that are often studied for their potential as EOR agents. Nanosilica can be used as an additive in EOR injection solutions, because it can interact with polymer molecules via hydrogen bonds and van der Waals interaction. Thus, the viscosity and thermal resistance of the polymer solution are expected to also increase. In addition to thermal and salinity resistance, it turns out that nanosilica can also increase the wettability of the rock surface by forming a nano-layer between the rock surface and the oil. This property can be analyzed by testing the contact angle alterations of the solution on a polar solid surface such as glass (SiO2). Increased wettability can reduce the adsorption rate of oil by rocks and facilitate oil mobility. In this study, a partially hydrolyzed polyacrylamide (PHPAM) was synthesized using the radical polymerization method (addition polymerization) and the partial hydrolysis method with alkaline solutions. The viscosity of the 1000 ppm PHPAM solution at 20 °C was measured at 166.69 mPa.s then increased to 173.48 mPa.s when 0.8% (w / w) of nanosilica was added. At a temperature of 80 °C, the viscosity of the solution with nanosilica reaches 147.14 mPa.s and only 120.8 mPa.s without nanosilica. To improve its characteristics, in this study a nanosilica surface